An amputation resets positional information to a proximal identity in the regenerating zebrafish caudal fin - Azevedo, Ana Sofia (2012)
We thank Lara Carvalho and Fabio Valerio for excellent zebrafish husbandry, Andreia Pinto for histology and Antonio Temudo for imaging support. We are grateful to C. Certal and S. Pascoal for comments on the manuscript. A. S. A and S. S were supported by FCT fellowships (SFRH/BD/33179/2007 and SFER/BD/32952/2006). L. S. was supported by two FCT grants (PTDC/SAU-OBD/64628/2006 and PTDC/SAU-OBD/100202/2008) and A.J. was supported by one FCT grant (PTDC/SAU-OBD/100200/2008).